RELIEF NARRATIVE ARJUNAWIWAHA DI GUA SELAMANGLENG DALAMPERSPEKTIF EDUKATIF - Y. Murdiyati Y. Murdiyati (LPMPP Universitas Negeri Yogyakarta, 2007)
Relief isonenf the decorations which was carved on the wall of temple.Themost of the relieves of East Java style have rather flatform as wayang, differentfrom the relieves of Centre Java style whichhave realistic form. There was the reliefnarrative Atjunawiwahawhich was carved on the wall of Selamangleng Cave,which havean education values which was necessary to the continue generation toface the epoch challange globalisation. Thismatter to remember the educationvalues of Indonesianmore pale. Although properly the .,ducation values whichwas still relevancewith the epoch development 2006/2007 percisted weredefended, and the culture which not relevance with the need of Indonesian societycould be left.In the asceticism scene contains belief in One God element, becausethe reached ofpurpose asceticism of was determined by the One God. It waslocation of the education value which was necessary planted to the children early.In the Goddess scenewas expressed freely and naturally. The describe of femalepersonwho tempts a male person, conform with the character of East Javaneseinclude the female person,who has the extrovert character. It's different from theCentre Javanesewho has the introvert character. There was also the ethic andaesthetic value, that was described in the Goddess scene with low level, it meansthey honor Atjuna. In the Bethara Guru scene gave a Pasopati heirloom to Arjunato killed Newatakawaca, indicated that Arjuna was responsible to reach thepurpose. The scene of Arjuna and Dewi Supraba went together to k.iIIedNewatakawaca, indecated there were an union and unit value between the Arjunaand Supraba. Thusin the relief of Selamangleng Cave contains a lot of educationalvalues which was necessary transmited to the continue generation